Patterns of risk exposure in first 1,000 days of life and health, behavior, and education-related problems at age 4.5: evidence from Growing Up in New Zealand, a longitudinal cohort study - Wallander, Jan L. (BMC Pediatr, 2021)
BACKGROUND: Children who are high priority candidates for early intervention need to be identified to reduce their risk for experiencing problems in development. Those exposed to multiple risk factors are more likely to exhibit problems in development than those exposed to a single or no risk factor. We examined the longitudinal associations between persistence and timing of exposure to cumulative risk (CR) on three occasions by age 2 and problems in development at age 4.5 in health, behavior, and education-related domains. METHODS: Data are from Growing Up in New Zealand (NZ), a prospective longitudinal study of a birth cohort first assessed during their last trimester in 2009–10 and followed at ages 9 months and 2 and 4.5 years. All women with an expected delivery date in a 12-month period who resided within a defined region were invited to participate, with no additional eligibility criteria. Exposure was measured for 12 sociodemographic and maternal health risk factors at third trimester and ages 9 months and 2 years, from which developmental trajectories were constructed capturing persistence and timing of CR exposure. Ten developmental outcomes were measured at age 4.5 to classify problems in overall health status, obesity, and injuries; internalizing and externalizing behavior problems; and letter naming, counting forward and backward, and expectations for starting school and completing education. RESULTS: Analyses of data from 6156 children (49% female, 33% Non-European ethnicity) who participated in the 4.5-age assessment uniformly showed associations between exposure to more than consistently zero CR across early development and higher prevalence of being classified with problems for 9 of 10 outcomes. Persistent exposure to a CR ≥ 4 was generally associated with a higher prevalence of problems for 7 of 10 outcomes, whereas the timing of first exposure to CR ≥ 4 showed a less consistent association with problem outcomes. CONCLUSIONS: These findings are concerning because over 50% of NZ children are exposed to at least one of these risk factors at some point in early development. Routine screening of most of these risk factors during pregnancy is feasible and can identify priority candidates for intervention.